Insights into the spreading of ataxin-2 through extracellular vesicles - Costa, Rafael Gomes da (2021)
Spinocerebellar ataxia type 2 (SCA2) is a neurodegenerative polyglutamine disease caused by an aberrant expansion of the trinucleotide CAG in the coding region of the ATXN2 gene. As a result, ataxin-2, the protein product resulting from this gene, harbors an abnormally expanded polyglutamine tract, which renders it more prone to aggregation and consequent formation of inclusion bodies within the brain of SCA2 patients. Moreover, a toxic gain-of-function of ataxin-2, accompanied by the reported toxicity of an ATXN2 antisense RNA, are thought to induce cellular alterations with subsequent neuronal death. Although only some neuroanatomical regions are primarily affected in SCA2, the neurodegeneration process seems to progress towards other brain regions, in latter stages of the disease. Nevertheless, the mechanisms responsible for this apparent disease spreading phenomenon have never been addressed. In the last decade, recurrent evidence has shown that extracellular vesicles (EVs) can mediate neuron-neuron transfer of aggregate-prone proteins associated with many neurodegenerative diseases. In some cases, it was also reported that this mechanism can induce toxicity in healthy recipient cells, suggesting an explanation for disease spreading. This study aimed to investigate the possibility of ataxin-2, in its protein and/or mRNA forms, being intercellularly transferred, similarly to what has been reported for proteins involved in neurodegenerative diseases. We show that eGFP-tagged ataxin-2 can be detected in non-transfected neuroblastoma cells when these are cultured in conditioned medium derived from eGFP-ataxin-2-transfected cells. Moreover, we show that ataxin-2 mRNA was found within two different types of extracellular vesicles, which were able to induce the formation of ataxin-2 aggregate-like structures within recipient cells, both in vitro and in vivo. Overall, this study suggests for the first time that EV-mediated transport of ataxin-2 mRNA can induce the formation of ataxin-2 aggregates in healthy recipient cells, possibly representing a novel mechanism involved in SCA2 pathogenesis.